2017
DOI: 10.21037/jgo.2017.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in bowel cancer

Abstract: Colorectal cancer is the third most common cancer in the United States and second leading cause of cancer death with over 50,000 patients expected to die from their disease in 2017. For patients who present at diagnosis with advanced disease the standard treatment is systemic chemotherapy. Over the last decade a number of biologic therapies have emerged as viable treatment options for advance colorectal cancer. When these new drugs are combined with chemotherapy survival is prolonged, often without a detriment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Emerging targeted biological and immune therapies are believed to maximize antitumor effects and minimize toxicity and risk of treatment failure. As such, they are intensively investigated, and novel potential molecular targets for antineoplastic therapy are looked for [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging targeted biological and immune therapies are believed to maximize antitumor effects and minimize toxicity and risk of treatment failure. As such, they are intensively investigated, and novel potential molecular targets for antineoplastic therapy are looked for [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have shown that biologic drugs, called "biologic" because they are produced by living organisms, may improve survival in patients with advanced colorectal cancer (CRC) (1)(2)(3)(4). One example is the pivotal study on bevacizumab published in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Biologic treatments comprise a wide group of compounds with natural origin produced by biotechnology and other cutting-edge technologies ( 14 ); yet, this term mainly refers to the subgroup of complex molecules representing targeted therapy, such as monoclonal antibodies and receptor fusion proteins ( 15 ). The last years have seen the emergence of biologic treatments for the treatment of several immune and oncologic disorders ( 16 – 18 ). The most extensively used are tumor necrosis factor-α (TNF-a) inhibitors, B-cell-targeted therapies, T cell co-stimulatory molecule blockers, and immune check point inhibitors.…”
Section: Introductionmentioning
confidence: 99%